2017
DOI: 10.4103/0976-237x.205045
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bracket surface morphology and dimensional change

Abstract: Objective:The objective of this study was to compare the surface morphology and dimensional stability of the bracket slot at the onset of treatment and after 12 months of intraoral exposure. The study also compared the amount of calcium at the bracket base which indicates enamel loss among the three orthodontic brackets following debonding after 12 months of intraoral exposure.Materials and Methods:The sample consisted of 60 (0.022” MBT) canine brackets. They were divided into three groups: self-ligating, cera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Comparing our results to previous research, slot height presented average height value grater than recommended (Bhalla, Good, McDonald, Sherriff, & Cash, ; Cash, Good, Curtis, & McDonald, ; Jones et al, ; Kusy & Whitley, ; Radhakrishnan et al, ; Zinelis, Annousaki, Makou, & Eliades, ). However, more recent research shows that the height of the slot presents with a lower average value, but still with significantly smaller negative deviation (Major, Carey, Nobes, & Major, ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Comparing our results to previous research, slot height presented average height value grater than recommended (Bhalla, Good, McDonald, Sherriff, & Cash, ; Cash, Good, Curtis, & McDonald, ; Jones et al, ; Kusy & Whitley, ; Radhakrishnan et al, ; Zinelis, Annousaki, Makou, & Eliades, ). However, more recent research shows that the height of the slot presents with a lower average value, but still with significantly smaller negative deviation (Major, Carey, Nobes, & Major, ).…”
Section: Discussionsupporting
confidence: 65%
“…However, these parameters may change during the manufacturing and finishing process, which may lead to modifications of the bracket's features, such as an increase or decrease in the slot height, as well as a loss of parallelism of the inner walls, resulting in converging or diverging of them. When these changes are present, fitting is not correct and the expected relationship between the wire and the bracket changes, thereby decreasing the efficiency of any type of mechanical treatment (Dolci, Spohr, Zimmer, & Marchioro, ; Radhakrishnan, Sapna Varma, & Ajith, ). Another change that may occur is related to the angle of torque, which can be increased or decreased since the bracket is intended to precisely fit on the buccal or lingual inclination of each dental element, thereby making it difficult to control some mechanical parameters (Dolci et al, ; Radhakrishnan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The two debracketing techniques were expected to result in different ARI scores. However, the ARI score and the presence of calcium were similar in the two methods, despite the difference in force applied, which was previously measured [15]. The explanation for this dichotomy is that the crack is probably initiated at the level of the adhesive layer and propagated at the bracket-adhesive or adhesiveenamel interface.…”
Section: Discussionmentioning
confidence: 63%
“…This is supported by a short-term study that showed that the rupture occurs at the bracket-adhesive interface [16]. Further recent studies [14,15] demonstrated that after a longer period of time, 24 months, the composite is completely polymerized with a strong adhesion force. Another aspect to consider is that the enamel under the sole of the bracket may be affected by decalcification resulting from food debris and poor hygiene that damages the enamel-adhesive bond.…”
Section: Discussionmentioning
confidence: 76%
“…Since SSCs are placed in the oral environment for several years and affected by physical and chemical factors such as saliva secretion, chewing, brushing, acidic beverages, abrasion and composition of biofilms, their surface changes. The changing of surface area, increases bacterial adhesion and surface roughness [27]. As a few cases of perforation have been seen in crowns, it was attempted to test the physical and mechanical properties of some brands of SSCs in the market.…”
Section: Introductionmentioning
confidence: 99%